2009
DOI: 10.1111/j.1476-5381.2009.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

A non‐apoptotic function of caspase‐3 in pharmacologically‐induced differentiation of K562 cells

Abstract: Background and purpose: Several anticancer drugs with diverse chemical structures can induce differentiation of cancer cells. This study was undertaken to explore the potential contribution of caspase-3 to pharmacologically-induced differentiation of K562 cells. Experimental approach:We assessed differentiation by measuring the expression of glycophorin A and haemoglobin synthesis in K562 cells treated with low concentrations of doxorubicin, hydroxyurea, cytosine arabinoside, cisplatin and haemin. Caspase-3 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 70 publications
(190 reference statements)
2
16
0
1
Order By: Relevance
“…As shown in Table 2, cells were strongly positive for CD71 and rarely positive for CD235a. Treatment with 40 μM hemin for 72 h did not change the MFI or the CD235a-positive rate, but increased the CD71-positive rate, as seen in previous studies in K562 cells [17,[23][24][25].…”
Section: Growth Potentialsupporting
confidence: 79%
See 1 more Smart Citation
“…As shown in Table 2, cells were strongly positive for CD71 and rarely positive for CD235a. Treatment with 40 μM hemin for 72 h did not change the MFI or the CD235a-positive rate, but increased the CD71-positive rate, as seen in previous studies in K562 cells [17,[23][24][25].…”
Section: Growth Potentialsupporting
confidence: 79%
“…This conclusion is compatible with the welldid not differ between T3-pretreated and control cells after hemin induction. This is probably because benzidine positivity with hemin treatment may be affected by free hemin diffusing into the cells, which may cause misleading results [25,29]. Overall, these findings indicate that T3 at a lower concentration acts as an enhancer of hemin and that 100 nM T3 blocks this effect in our model of erythroid differentiation.…”
Section: Resultsmentioning
confidence: 86%
“…Additionally, we show that hnRNP K is not ubiquitinated in K562 cells and proteasome inhibitors fail to stabilize the protein. Caspases not only catalyze site-specific protein cleavage in apoptosis, 11 but were also shown to be activated in terminal erythroid differentiation, 12, 13, 14 which is not associated with apoptosis. 15 Interestingly, a specific N-terminal hnRNP K fragment that migrates at 48 kD accumulates during erythroid differentiation.…”
mentioning
confidence: 99%
“…1A. The range of the Ara-C dose and time of incubation for erythroid differentiation was based on the results published by Sztiller-Sikorska et al (8). Based on the data presented in Fig.…”
Section: Ed 50 Of Ara-c Is Increased In K562 Pu1kd Cellsmentioning
confidence: 99%
“…Several studies indicated that low concentrations of cytosine arabinoside (Ara-C) induce erythroid differentiation of K562 cells (7,8). In this study, we investigated whether the effects of Ara-C are also associated with the expression level of PU.1.…”
Section: Introductionmentioning
confidence: 97%